Mission Power and Firm Financial Performance (2017)
We estimate the effect from mission statement on firm financial performance in a sample of Colombian companies. The mission power, a latent variable defined by using tools from word content analysis, is included in a structural equation model to compute its impact across two channels: the profit margin and the assets turnover. Our estimates show that the no-significant impact of mission statement, which is documented in the literature, may be caused by the opposite effect that sales amount induces on both channels. We disentangle both effects and show that the assets turnover dominates which suggest that the mission statement compels good assets management practices.